2017
DOI: 10.31219/osf.io/xv4np
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Esteem and Relationship Satisfaction during the Transition to Motherhood

Abstract: In the current study, we examined longitudinal associations between romantic relationship satisfaction and self-esteem before and after childbirth in subgroups of first-, second-, third-, and fourth-time mothers.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 58 publications
(83 reference statements)
2
49
0
Order By: Relevance
“…Whereas these gradual decreases were unexpected, they were in line with some previous studies that showed decreases in new parents' conscientiousness Specht et al, 2011) and mothers' self-esteem van Scheppingen et al, 2018) in the years after childbirth.…”
Section: Socialization Effectssupporting
confidence: 75%
See 3 more Smart Citations
“…Whereas these gradual decreases were unexpected, they were in line with some previous studies that showed decreases in new parents' conscientiousness Specht et al, 2011) and mothers' self-esteem van Scheppingen et al, 2018) in the years after childbirth.…”
Section: Socialization Effectssupporting
confidence: 75%
“…Recently, however, several longitudinal studies have examined the associations between parenthood and Big Five personality traits (e.g., van Scheppingen et al, 2016;Denissen, Luhmann, Chung, Bleidorn, 2018) as well as self-esteem van Scheppingen et al, 2018). We refer to the results of this line of research in deriving hypotheses concerning both cross-sectional and longitudinal associations between self-control and parenthood.…”
Section: Previous Research On Parenthood and Personality Changementioning
confidence: 99%
See 2 more Smart Citations
“…Theory and research suggests that life events can impact change in self-esteem. However, most of this research has focused on events that typically occur during early adulthood, such as college, marriage, or parenthood (e.g., van Scheppingen, Denissen, Chung, Tambs, & Bleidorn;in press). In contrast, we have a limited understanding of how life events affect self-esteem in late adulthood.…”
mentioning
confidence: 99%